Capsaicin 8% Patch Untuk Terapi Alternatif Pada Nyeri Neuropati Diabetikum Perifer - Muhammad Luthfi Adnan (Warmadewa University, 2021)
Abstract Diabetes is one of the most common health problems due to its high incidence and complications. One of the complications associated with diabetes is painful diabetic peripheral neuropathy (PDPN). The capsaicin 8% patch is a localized pain treatment that provides effective pain relief from a single application in patients with peripheral neuropathic pain. The aim of this review is to discuss the effect of capsaicin patch 8% in patients with painful diabetic peripheral neuropathy. The search strategy was conducted in PubMed and modified for other databases. The search was limited to English-language reports. The keywords used were